MICROWAVE IRRADIATION PROCESS FOR BIODIESEL PRODUCTION USING WASTE SUGARCANE BAGASSE DERIVED ACID ACTIVATED CATALYST - NAZIR, MUHAMMAD HAMZA (2021)
Production of biodiesel has been increased globally during the last decade to overcome the problems of increasing prices of petro-diesel and depletion of fossil fuels. The production of biodiesel using homogeneous or heterogeneous catalysts is not favorable due to difficult catalyst recovery, purification of the product in case of homogeneous catalysts and longer reaction time, severe reaction conditions and high production cost are the drawbacks of heterogeneous catalysts. The focus of this study is to utilize agro-waste sugarcane bagasse in the synthesis of heterogeneous catalyst for biodiesel production from waste feedstock i.e., waste cooking oil which is leftover on a large scale after cooking and frying purposes. Waste sugarcane bagasse was converted into biochar through partial carbonization and activated through sulfonation at given reaction conditions. The prepared catalysts were found to be thermally stable up to 500 as observed by thermogravimetric analysis. Attachment of functional groups (-COOH, -OH, SO3H) was confirmed by fourier transform infrared spectroscopy, porous structure after sulfonation by scanning electron microscope, amorphous nature by x-ray diffraction and amount of carbon, hydrogen, nitrogen, and sulfur was determined by CHNS analyzer. The prepared catalyst exhibited an excellent surface area (20.78 m2. g-1) as determined by BET and total acid density 3.94 mmol. g-1. The process of biodiesel production was done in a modified microwave reactor equipped with thermocouple to maintain temperature and condenser to avoid the evaporation of solvent. The maximum conversion of triglycerides 95.45% and biodiesel yield of 92.12% was obtained at 60 ℃ with 5 wt.% of catalyst using 15:1 of methanol to oil molar ratio after 15 minutes. The results of experiments were validated by using response surface methodology based on the selected quadratic model with a confidence level of (R2= 0.92). Kinetic studies of the experiments depicted that the use of sulfonated catalyst lowered the activation energy (10.5 kJ. mol-1) and reactants attained equilibrium point after a short interval of time under microwave heating.